- 1-800-665-6601
- [email protected]

The given equation is 7x + 7 = 5x + 9

We can add -7 on both sides of the above equation

Now we can write 7x + 7 – 7 = 5x + 9 – 7

We have the equation 7x = 5x + 2, next we can add – 5x on both sides

7x – 5x = 5x + 2 – 5x

Therefore, 2x = 2 => x = 1

We have 2 linear equation 2x + y =2 and x + y = 2

From the first equation we can write y = 2 – 2x, now we can plug in the second equation

Therefore, x + 2 – 2x = 2

Now we can simplify this as, -x = 0 => x = 0

Then we can plug this x value in the first or second equation

x + y = 2 => 0 + y = 2 => y = 2